IMPLEMENTASI PENGGAMBARAN, PENJADWALAN, DAN ESTIMASI BIAYA DENGAN METODE BIM - Yogie Risdianto; Hariz Fardiaz Dwi Septiawan (CRANE: Civil Engineering Research Journal, 2026)
The implementation of Building Information Modeling (BIM) technology in building construction projects is rapidly evolving, driven by the need for improved efficiency, accuracy, and collaboration in project management. This research aims to analyze the implementation of BIM in its 3D to 5D dimensions within construction at the Faculty of Vocational Management, Airlangga University Gresik. The research methodology employed in this study integrates two primary approaches: a literature review and the application of a Building Information Modeling (BIM) system using Autodesk Revit software. The application of Building Information Modeling (BIM) in construction projects, particularly in the Management Faculty Vocational Building Construction Project at Airlangga University in Gresik, demonstrates efficiency across various aspects. The utilization of BIM 4D and 5D, which combines 3D models from Autodesk Revit with Microsoft Project schedules into Autodesk Navisworks, facilitates realistic construction phase visualization and simulation, as well as direct project cost monitoring. The comparison results show a 6.86% efficiency in cost estimation between conventional methods and BIM methods, which aligns with previous research indicating the cost estimation efficiency of the BIM method. The discrepancy between planner drawings and budget estimates in conventional methods indicates that the BIM method can serve as a control to ensure alignment between drawing volumes and cost estimates. The findings of this study suggest that the integration of BIM technology effectively reduces design error risks and minimizes resource waste, positively impacting construction cost management.